2012
DOI: 10.4317/medoral.17429
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength of quartz fiber posts to root canal dentin using total-etch and self-adhesive resin cements

Abstract: Objectives: Several adhesive systems are available for cementation of fibre posts into the root canal. The aim of the present study was to investigate the push-out bond strengths of quartz fibre posts to root dentin with the use of different total-etch and self-adhesive resin cements. Study Design: Ninety single-rooted human premolars were endodontically treated and standardized post-spaces were prepared. Fibre posts were cemented with different luting agents: total-etch (Nexus NX3, Duo-Link, and RelyX ARC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
3
25
2
9
Order By: Relevance
“…Results of this study expressed that bond strength of FRC posts to radicular dentin in total-etch cement is lower than the self-etch cement. We can explain that the narrow canal holds water by surface tension, making it difficult to replace water with bonding agents .Therefore, enhanced moisture content inside the root canal might have led to reduced bond strength values of total-etch systems, even though the root canals were dried carefully using paper points (5) .The results of studies carried out by Goracci et al (16) and Mazzoniet et al (8) are in contrast to our finding. The reason for this controversy could be the type of cements and duration of curing.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Results of this study expressed that bond strength of FRC posts to radicular dentin in total-etch cement is lower than the self-etch cement. We can explain that the narrow canal holds water by surface tension, making it difficult to replace water with bonding agents .Therefore, enhanced moisture content inside the root canal might have led to reduced bond strength values of total-etch systems, even though the root canals were dried carefully using paper points (5) .The results of studies carried out by Goracci et al (16) and Mazzoniet et al (8) are in contrast to our finding. The reason for this controversy could be the type of cements and duration of curing.…”
Section: Discussioncontrasting
confidence: 94%
“…The self-adhesive cements do not require any pretreatment of the tooth substrate, once the cement is mixed, the application is accomplished in a single clinical step. (5) There are some controversies about the efficacy of these cements. (2,(6)(7)(8)(9)(10)(11)(12) Therefore, the aim of the present study was to compare the push-out bond strength of FRC posts to root dentin using four different adhesive cements with different mechanisms of adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The bond strength of cement/post/dentin interface can be influenced by resin cement flowability, cement distribution in coronal, middle, and apical thirds of the root, the anatomy of the canal, and the orientation of the dentinal tubules [5,13,[20][21][22][23]. In the present study, there was no significant difference in the bond strength between the Centrix syringe or Lentulo drill technique, corroborating the findings of previous studies [14,[17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…[1314] The results showed that the mean push-out bond strength value of the SDR group was higher than that of the X-Post group; however, no statistically significant difference ( P > 0.05) was observed. These values were higher than the values of a previous study, which used the SDR as luting cement and were lower than the values of the other study.…”
Section: Discussionmentioning
confidence: 99%